Model Problem Based Learning Berbantuan Simulasi Komputer Untuk Meningkatkan Penguasaan Konsep Pada Materi Alat-Alat Optik - Khairun Niami; Kosim Kosim; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This research aims to determine the increase in mastery ofÃÂ  concept through ÃÂ problem based learning model assisted by computer simulations on the material of class XI optical devices in SMAN 8 Mataram. This type of research is quasi-experimental with pretest-posttest control group design. The research population was all students of class XI MIA SMAN 8 Mataram. Sampel taken using purposive sampling technique. Students of class XI MIA 1 were selected as experimental class and class XI MIA 2 as control class. Hypothesis testing using t test with a significance level of 5% assisted by SPSS 23. Hypothesis testing yielded a significance level of 0.010 for mastery of concepts smaller than 0.05. Based on the provisions, Ho is rejected and it can be concluded that there is an influence of problem based learning models assisted by computer simulations on the mastery of the concepts. This result can be proved by the N-gain test, where there is an increase in mastery of concepts by using a problem based learning model assisted by computer simulations. The highest increase in sub-material for concept mastery data was seen in the reflection devices and lowest sub-material in binocular.